Parametric analysis of transient skin heating induced by terahertz radiation. Issue 5 (10th February 2014) - Zilberti, Luca; Arduino, Alessandro; Bottauscio, Oriano; Chiampi, Mario
<x xml:space="preserve">Abstract</x> This paper investigates the effect of relevant physical parameters on transient temperature elevation induced in human tissues by electromagnetic waves in the terahertz (THz) band. The problem is defined by assuming a plane wave, which, during a limited time interval, normally impinges on the surface of a 3‐layer model of the human body, causing a thermal transient. The electromagnetic equations are solved analytically, while the thermal ones are handled according to the finite element method. A parametric analysis is performed with the aim of identifying the contribution of each parameter, showing that the properties of the first skin layer (except blood flow) play a major role in the computation of the maximum temperature rise for the considered exposure situation. Final results, obtained by combining all relevant parameters together, show that the deviation from the reference solution of the maximum temperature elevation in skin is included in the coverage intervals from −30% to +10% at 0.1 THz and from −33% to +18% at 1 THz (with 95% confidence level). These data allow bounding the possible temperature increase against the spread of tissue properties that could be reasonably used for dosimetric simulations. Bioelectromagnetics. 35:314–323, 2014. © 2014 Wiley Periodicals, Inc.